Antifungal Drugs for Invasive Candida Infections (ICI) in Neonates: Future Perspectives - Bersani, Iliana; Piersigilli, Fiammetta; Goffredo, Bianca Maria; Santisi, Alessandra; Cairoli, Sara; Ronchetti, Maria Paola; Auriti, Cinzia (Frontiers in Pediatrics, 2019)
Fungal infections may complicate neonatal clinical course and the spectrum of therapies for their treatment in the perinatal period is limited. Polyenes, Azoles and Echinocandins represent the three classes of antifungal drugs commonly used in the neonatal period. The present review provides an overview about the most recent therapeutic strategies for the treatment of fungal infections in neonates.